Food versus fuel: Examining tradeoffs in the allocation of biomass energy sources to domestic and productive uses in Ethiopia - Mekonnen, Dawit Kelemework; Bryan, Elizabeth; Alemu, Tekie; Ringler, Claudia (Wiley, 2017)
Rural households in Ethiopia have limited options to meet their domestic energy needs because they lack access to modern fuels and technologies. Domestic use of certain fuel sources, such as cow dung, can hinder agricultural outcomes and productivity. This article explores the tradeoffs between domestic and productive uses of biomass energy sources in the Nile Basin of Ethiopia using a nonseparable farm household model where labor allocation to energy collection and farming are analyzed simultaneously. We estimate a system of five structural equations using three‐stage least squares and find that the use of dung as a domestic fuel source has negative implications for the value of harvested crops, while use of on‐farm fuelwood is associated with increased value of agricultural output. On‐farm production of fuelwood appears to increase the value of crop output and provide labor savings, by making fuelwood collection more convenient for households. Policy interventions to support the expansion of agroforestry and increase access to new energy‐efficient technologies are needed to ensure that agricultural productivity can be both increased and sustained.